2018
DOI: 10.1242/jeb.190892
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of linear acceleration in bluegill sunfishLepomis macrochirus

Abstract: In their natural habitat, fish rarely swim steadily. Instead they frequently accelerate and decelerate. Relatively little is known about how fish produce extra force for acceleration in routine swimming behavior. In this study, we examined the flow around bluegill sunfish Lepomis macrochirus during steady swimming and during forward acceleration, starting at a range of initial swimming speeds. We found that bluegill produce vortices with higher circulation during acceleration, indicating a higher force per tai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
5
14
0
Order By: Relevance
“…Trout produced a mean thrust of 1.5 ± 0.4 mN. All values were on the same order of magnitude as previous estimates from wake analyses (39,40). Fig.…”
Section: Resultssupporting
confidence: 82%
“…Trout produced a mean thrust of 1.5 ± 0.4 mN. All values were on the same order of magnitude as previous estimates from wake analyses (39,40). Fig.…”
Section: Resultssupporting
confidence: 82%
“…This finding was corroborated by detailed analyses of bluegill sunfish showing increased head and tail amplitudes [7] and lamprey showing higher amplitudes along the entire body [6] during linear acceleration. Wise et al [7] also found indications of larger force production rather than the reorientation of axial forces during acceleration compared to steady swimming patterns, which differs slightly from the conclusions of [5] who documented vortex wake reorientation during acceleration. Whereas fish show increased tail beat amplitudes during linear accelerations, Akanyeti et al [5] also showed that different amounts of accelerations are largely modulated by the tail beat frequency.…”
Section: Introductionsupporting
confidence: 54%
“…Wise et al . 52 showed that the acceleration reaction in bluegill sunfish is increased by the very same kinematics bluegill sunfish use during accelerations. It may be that fishes can produce these additional forces economically by using eccentric activity.…”
Section: Discussionmentioning
confidence: 92%
“…Even the red muscle studied here probably still generates net positive power, because it remains active for the same amount of time during shortening. To accelerate in a fluid, bluegill sunfish require a force both to accelerate their own mass, but also to overcome the acceleration reaction 52 , an additional force required to accelerate the fluid around them 53 . Wise et al .…”
Section: Discussionmentioning
confidence: 99%